Introduction to William James An Essay and Selected Texts - Reck, Andrew J. (Indiana University Press, 1967)
In an extended essay with related texts, Mr. Reck presents a reappraisal of James' work which offers an excellent introduction to one of the most fertile and original minds America ever produced. An eight-part essay parallels and offers commentary on selections from Principles of Psychology, Briefer Course, Essays in Radical Empiricism, The Will to Believe, The Varieties of Religious Experience, Pragmatism, and A Pluralistic Universe. The author closely examines James' intellectual development, emphasizing the influence of his European education and experience, and assesses his relevance to contemporary philosophy. He also provides notes, a chronology of James' life, and a bibliography.